A spatial decision support system for traffic accident prevention in different weather conditions - Ivajnšič, Danijel (Acta geographica Slovenica, 2021)
Natural conditions play an important role as determinants and cocreators of the spatiotemporal road traffic accident Hot Spot footprint; however, none of the modern commercial, or open-source, navigation systems currently provides it for the driver. Our findings, based on a spatiotemporal database recording 11 years of traffic accidents in Slovenia, proved that different weather conditions yield distinct spatial patterns of dangerous road segments. All potentially dangerous road segments were identified and incorporated into a mobile spatial decision support system (SLOCrashInfo), which raises awareness among drivers who are entering or leaving the predefined danger zones on the street network. It is expected that such systems could potentially increase road traffic safety in the future.
Keywords: GIS; mobile application; mobilna aplikacija; prometna varnost; prostorske podatkovne baze; prostorski vzorci; spatial databases; spatial patterns; traffic safety